2009
DOI: 10.1183/09059180.00003709
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical reactions in non-HIV tuberculosis presenting as endobronchial obstruction

Abstract: Paradoxical reaction (PR) in tuberculosis (TB) is common and may affect up to 25% of patients. PR has the potential to cause significant morbidity and, on occasion, death. Although PR has been recognised for some time, the pathophysiology, especially in HIV-negative patients, is not well understood.We present two cases of PR in HIV-negative patients with TB presenting as significant airway obstruction secondary to a florid endobronchial component.These cases demonstrate that PR should be considered in all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
0
19
0
1
Order By: Relevance
“…However, diagnosis is challenging; a change in the size of ulcers on an uneven surface such as that of a limb is difficult to record, and erythema is easily missed on black African skin. By analogy with other diseases such as tuberculosis, these reactions are thought to result from increasing inflammation as a consequence of enhancement of the immune response during treatment (28)(29)(30)(31). In the present study, paradoxical reactions were observed in 9% of patients with all forms of Buruli ulcer disease from week 4 during antibiotic treatment up to week 32, 24 weeks after treatment finished.…”
Section: Discussionmentioning
confidence: 66%
“…However, diagnosis is challenging; a change in the size of ulcers on an uneven surface such as that of a limb is difficult to record, and erythema is easily missed on black African skin. By analogy with other diseases such as tuberculosis, these reactions are thought to result from increasing inflammation as a consequence of enhancement of the immune response during treatment (28)(29)(30)(31). In the present study, paradoxical reactions were observed in 9% of patients with all forms of Buruli ulcer disease from week 4 during antibiotic treatment up to week 32, 24 weeks after treatment finished.…”
Section: Discussionmentioning
confidence: 66%
“…Bu nedenle PR şüphesi olduğunda, tedavi uyumsuzluğu, ilaç direnci, hastalığın progresyonu ve sekonder sebepler mutlaka ekarte edilmelidir. [12] Olgumuz ilaçlarını düzenli olarak kullandığından, tedavi uyumsuzluğu düşünülmedi. Ancak hastaneye başvuru sırasında ayırıcı tanıda düşünülen malignite veya diğer enfeksiyonlar yeniden gözden geçirildi.…”
Section: Discussionunclassified
“…4g, 4h) is rare. It can either be a newly developed paradoxical lymphadenitis with erosion or fistulation into the airways or a true de novo endobronchial paradoxical reaction (15).…”
Section: Clinical and Radiologic Manifestations Of Tb-irismentioning
confidence: 99%
“…Systemic corticosteroid administration for 4-6 weeks has been shown to be effective in HIV, symptomatic enlarging intracranial tuberculoma (16), and endobronchial obstruction (15), since it may reduce proinflammatory cytokines (16,17). However, its role in other forms of TB-IRIS remains unclear.…”
Section: Treatment and Outcomesmentioning
confidence: 99%